Zakat Untuk Mengurangi Angka Ketergantungan Ekonomi Dengan Penyaluran Model Usaha Produktif - Mochlasin Mochlasin (State Institute of Islamic Studies (IAIN) Salatiga, 2018)
The discussion in this paper covers: What is the motive for establishing zakat institutions in Pulosari, Jumoyo, Salam, Magelang? How is the collection mechanism? How is the distribution model? This research type was field research with data collection technique through observation, interview and documentation. The result of this research found that the distribution of productive zakat is done in three ways. First, model in kind, that BAZIS manager gave zakat as capital without having to return and without bond, Second, non-financial mudharabah model, the BAZIS manager gives goat breeding, if the goat gives birth to the child a mustahiq right while the indutility is returned to be distributed to other mustahiq. Third, al-qard al-hasan model, amil channeling zakat property in the form of capital to mustahiq with provisions for returning capital.